Condylar hyperplasia: characteristics, manifestations, diagnosis and treatment. a topic review - López-Buitrago, Diego Fernando; Corral-Saavedra, Claudia Marcela (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Condylar hyperplasia is a condition that affects not only the proportions and facial symmetry in patients, but also static and dynamic occlusion functions with repercussions in the masticatory activity, the health of the temporomandibular joint (TMJ), and the anatomy and volume of adjacent soft tissues. Therefore, according to its severity this disease concerns maxillofacial surgeons, orthodontists, physical therapists, plastic surgeons, and nuclear doctors, who are all closely involved in the diagnosis stage. Historically, diagnosis of condylar hyperplasia has been based on anamnesis and the initial physical examination of the patient, where asymmetry, malocclusion and in some cases temporomandibular disorders (TMDs) are detected and later confirmed with tests such as bone scan and eventually by pathology report once condylar surgery has been done. The purpose of this literature review is to provide detailed information on the behavior of this disease from the point of view of its etiology, clinical characteristics, and distribution by age, sex and affected condyle, as well as the necessary diagnostic and imaging aids for its diagnosis, differential diagnosis, associated diseases, histological characteristics of the affected tissues, and the different therapeutic approaches according to severity, patient’s age, and active or inactive form of the condition. The information was obtained from scientific research articles in different journals and literature reviews, taken from databases such as MEDLINE, EMBASE, and PubMed.